2005
DOI: 10.1097/01.shk.0000150779.47107.d5
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Pretreatment May Protect Against Heatstroke-Induced Circulatory Shock and Cerebral Ischemia by Reducing Oxidative Stress and Energy Depletion

Abstract: The mechanisms underlying the protective effects of heat shock pretreatment on heatstroke remain unclear. Here we attempted to ascertain whether the possible occurrence of oxidative stress and energy depletion exhibited during heatstroke can be reduced by heat shock preconditioning. In the present study, colonic temperature, mean arterial pressure, heart rate, striatal levels of heat shock protein 72 (HSP72), local Po2, brain temperature, cerebral blood flow, cellular ischemia and damage markers, dihydroxybenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 40 publications
6
47
2
2
Order By: Relevance
“…Passive exposure of laboratory rats to environmental heat results in an increase in Hsp-72 expression in most of the organs proportional to the severity of the heat stress (Blake et al 1990;Flanagan et al 1995), while pre-induction or over-expression of Hsp-72 prevents organ damage and lethality (Yang and Lin 1999;Wang et al 2005; Lee et al 2006). In humans, exercise associated heat stress was shown to be a potent inducer of Hsp-72 expression and release into the circulation (Moseley 1997;Febbraio and Koukoulas 2000;Walsh et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive exposure of laboratory rats to environmental heat results in an increase in Hsp-72 expression in most of the organs proportional to the severity of the heat stress (Blake et al 1990;Flanagan et al 1995), while pre-induction or over-expression of Hsp-72 prevents organ damage and lethality (Yang and Lin 1999;Wang et al 2005; Lee et al 2006). In humans, exercise associated heat stress was shown to be a potent inducer of Hsp-72 expression and release into the circulation (Moseley 1997;Febbraio and Koukoulas 2000;Walsh et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental studies suggest that heat shock response is an important component in the pathogenesis of heatstroke (Flanagan et al 1995;Moseley 1997;Welch 2001;Wang et al 2005). Passive exposure of laboratory rats to environmental heat results in an increase in Hsp-72 expression in most of the organs proportional to the severity of the heat stress (Blake et al 1990;Flanagan et al 1995), while pre-induction or over-expression of Hsp-72 prevents organ damage and lethality (Yang and Lin 1999;Wang et al 2005; Lee et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…35 It has been demonstrated that heat shock pretreatment induces Hsp72 overexpression in striatum and confers protection against heatstroke-induced arterial hypotension, striatal ischemia, and damage by reducing oxidative stress and energy depletion. 36 A growing body of evidence also suggests the role for HSPs in the whole organism's adaptation to heat other than through thermotolerance. In fact, in addition to the rapid heat shock response, chronic exposure to moderate heat may induce HSP accumulation, and since HSPs overexpression in cultured cells elevate the degree of the lethal temperature, their accumulation on long-term heat acclimatization could also contribute to the elevation of the upper body core temperature safety margin and reduce heat illness risk.…”
Section: Role Of Hsps In Heat Adaptation and Protection Against Heatsmentioning
confidence: 99%
“…Lipid peroxidation was assessed by measuring the levels of brain (or hypothalamus) malondialdehyde (MDA) with 2-thiobarbituric acid (TBA) (Sigma) to form a chromophore absorbing at 532 nm (34). About 0.1 g of tissue was homogenized with 1.5 ml of 0.1 M phosphate buffer at pH 3.5.…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%